Minimum periodic function test of HPGe Detector Using 152Eu Certified Reference Materials - Yogi Priasetyono; Wahyu Retno Prihatiningsih (Wahana Fisika, 2020)
The purpose of this research is to determine a minimum of periodic function tests for measurement validation for environmental samples. In this paper, the EU 152 is used as a source for measuring energy calibration as well as efficiency. Control quality on energy calibration monitor channel changes in energy 121.78 keV. In addition to calibration, testing Minimum Detectable Activity on this system. Results from measurements are then validated using environmental samples.